2016
DOI: 10.1007/s11356-016-7399-1
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of orange dyes and carbamazepine by soybean peroxidase immobilized on silica monoliths and titanium dioxide

Abstract: In this paper, the removal of three common dyes (orange I, orange II, and methylorange) and of the anticonvulsant drug carbamazepine from aqueous solutions by means of enzymatic and photocatalytic treatment was studied. Soybean peroxidase (SBP) was used as biocatalyst, both free in solution and immobilized on silica monoliths, and titanium dioxide as photocatalyst. The combination of the two catalysts led to a faster (about two to four times) removal of all the orange dyes compared to the single systems. All t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 48 publications
(53 reference statements)
4
26
0
Order By: Relevance
“…For the extraction of soybean peroxidase (SBP) (Tolardo et al, 2019 ), the seeds were peeled, and the obtained hulls were stored at −12°C until use. SBP was extracted and purified by a process based on a previously published method (Calza et al, 2016 ): 100 g of soybean hulls were ground in a mortar, added to 600 mL of phosphate buffer (0.025 M, pH 7) and left under stirring for 2 h at room temperature. Then, the hulls were separated from the solution by filtration with a cotton gauze and subjected to the same treatment until the filtrate gave a negative response to enzymatic activity test for SBP.…”
Section: Methodsmentioning
confidence: 99%
“…For the extraction of soybean peroxidase (SBP) (Tolardo et al, 2019 ), the seeds were peeled, and the obtained hulls were stored at −12°C until use. SBP was extracted and purified by a process based on a previously published method (Calza et al, 2016 ): 100 g of soybean hulls were ground in a mortar, added to 600 mL of phosphate buffer (0.025 M, pH 7) and left under stirring for 2 h at room temperature. Then, the hulls were separated from the solution by filtration with a cotton gauze and subjected to the same treatment until the filtrate gave a negative response to enzymatic activity test for SBP.…”
Section: Methodsmentioning
confidence: 99%
“…In the last decades, new chemicals were detected in wastewaters as a result of new industrial processes and increased consumption of pharmaceuticals and personal care products [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Out of methods listed above, the adsorption technique [14] has attracted considerable attention because of the simple procedures needed, because no toxic substances are produced, because of ability to treat concentrated forms of the pollutants, and to reuse the spent adsorbent via regeneration. Moreover, it plays a central role in drinking water purification and wastewater treatments [3,7,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Many authors showed the effectiveness of SBP in the oxidation of chlorophenols [14][15][16][17][18]. The ability of SBP in the degradation of 2,4,6-trichlorophenol (TCP) was previously studied by Calza et al [19] using composite material under UV irradiation.…”
Section: Introductionmentioning
confidence: 99%